ANALISIS STRATEGI SEGMENTING, TARGETING DAN POSITIONING PADA PERUSHAAN ASURANSI PT.(PERSERO) JIWASRAYA, PEKANBARU - Sihotang, Jon Predianto; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aims to identify and analyze the strategy of segmenting, targeting and positioning on the insurance company PT.(Persero) Asuransi Jiwasraya, Pekanbaru. In last 5 (five) years, the company experienced with unstable marketing. And the author believes that the trouble sits inside the marketing strategies that are not running well. The data had gained directly from the key informans by interviewing process in having accurate informations.The method of this research was used descriptive analysis that explains the overview of this research reference to explored variables and accompanied by decipherment based to research results. Then, the reduction, presentation, and making conclusions was needed to sharpen the writing of the result of the study.This research concluded that Asuransi Jiwasraya divides its market demographically based on employment background there are private employees, students, doctors and state employees. In determining of the target market, the company applies a full market coverage formula, that means the company serves whole costumers regardless any aspects. In positioning the company into the minds of consumers, the company always indicate that this company also run with public interest, gives benefits, guaranteed after sales, and affordable price of products.Keywords: segmenting, targeting, positioning